SURFACE ENHANCEMENT AND TOOL LIFE INVESTIGATIONS OF FRICTION STIR WELDING TOOL - EMAMIAN, SEYED SATTAR (2018)
Welding matrix composites with conventional methods produces many discontinuities which harms the quality of joints. Friction stir welding offers an alternative method to prevent these issues.